LEGALITAS BADAN USAHA MANDIRI TERPADU (BMT) SEBAGAl LEMBAGA KEUANGAN MIKRO BERDASARKAN HUKUM DI INDONESIA - ARI RAHMAD HAKIM BUDIAWAN FIRDAUS; YUDHI SETIAWAN; I GUSTI AGUNG WISUDAWAN (Universitas Mahasaraswati Mataram, 2021)
The existence of Baitul Maal wa Tamwil (BMT) as a microfinance institution in Indonesia has a very strategic position and role, this is not an exaggeration because in reality as a microfinance institution, BMT supports the community's economy, especially small or micro-entrepreneurs and the community. low-income earners in general who mostly live in rural areas. The existence of BMTs that is integrated with the lives of low-income people is one of the distinct advantages of this financing institution so that it makes it easier for the poor to access funding. Thus it can be said that BMT has a very important position and role because in its development it continues to increase significantly as a Micro Financial Institution, both in terms of financial performance and the number of customers that are not accessible to existing banking institutions. However, with this important existence and role, every BMT should pay attention to both institutional and operational legality aspects that must exist in him, so that the legal existence of all service products offered and guaranteed application of sharia principles in their activities